ANTIOXYDANTS ET PHYTOCHELATINES DANS LA TOLERANCE ET L’ACCUMULATION DU MANGANESE CHEZ L’HIBISCUS SABDARIFFA LINN. - Younes, Mavoungou Ange; Nicaise, Lepengue Alexis; Bertrand, M’batchi (European Scientific Journal, ESJ, 2015)
After 12 days of culture seeds roselle (Hibiscus sabdariffa L.) growth chamber, seedlings are subject to the effect of manganese concentration (2,9μM) to study the accumulation of Mn and its toxicity for 24 hours (1 day). The results show that Mn accumulates extensively in the shoot than in the roots, photosynthetic pigments (chloro (a) and carotenoids) and the enzyme system (SOD, CAT and GPOX) increase during 24 hours of experience. In shoot, SOD and CAT enzyme activity is higher than that APX, GR and GPOX. In roots, SOD enzyme activity and GPOX is higher than APX, GR and CAT. The amount of glutathione (GSH) and phytochelatin (PCs) are measured to monitor their responses detoxification under exposure levels of Mn in the plant. The maximum synthesis PCs rise to 24 hours of exposure to Mn. This correlates with reduced GSH. This shows that a protective mechanism that chelate excess Mn out of the metabolic center is set up by the plant. Hibiscus sabdariffa Linn therefore has the ability to accumulate and tolerate concentrations of Mn in the first hour of exposure by controlling the rate of GSH and PCs.